Acknowledgments - Anderson, Kate (YA Hotline, 2022)
First, we would like to acknowledge that Dalhousie University is located in Mi’kma’ki, the ancestral and unceded territory of the Mi’kmaq. We are all Treaty people.Our group would like to thank you, dear reader. It is because of you that we curated and made this Escapism issue of the YA hotline. Without you, none of this would be possible. We truly hope that this issue can bring you some comfort and joy during this especially uncertain and difficult times, and remember, we are in this together.